Hsa_circ_0107593 Suppresses the Progression of Cervical Cancer via Sponging hsa-miR-20a-5p/93-5p/106b-5p - Liao, Wenyan; He, Jun; Disoma, Cyrollah; Hu, Yi; Li, Junhua; Chen, Guodong; Sheng, Ying; Cai, Xinyu; Li, Chuanfu; Cheng, Kai; Yang, Chunfen; Qin, Yongxi; et al. (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are a new class of single-stranded RNAs that form a continuous loop with crucial role in regulation of gene expression. Because their circular conformation conforms numerous properties, circRNAs have been investigated recently to demonstrate their important role in the development and progression of various cancers. However, the function of circRNAs and their regulatory outcomes in cervical cancer (CC) have rarely been explored. In this study, the role and molecular mechanism of hsa_circ_0107593 in cervical cancer are demonstrated. Quantitative polymerase chain reaction (qRT-PCR) was used to determine the expression of hsa_circ_0107593 and three miRNAs (hsa-miR-20a-5p, 93-5p, and 106b-5p) in paired CC tissues (tumor tissue vs. adjacent normal cervical tissue), CC cell lines, and human normal cervical epithelial immortalized cell line. A series of functional experiments were conducted to assess the function of hsa_circ_0107593 in CC development. The Receiver Operating Characteristic (ROC) curve was plotted to estimate the diagnostic value of hsa_circ_0107593 in CC. The dual-luciferase reporter assay was used to explore the interaction between hsa_circ_0107593 and hsa-miR-20a-5p/93-5p/106b-5p. Bioinformatic analysis was conducted to predict the target mRNAs, pathways, and functional enrichment. The results revealed that hsa_circ_0107593 has low expression in CC tissues and CC cell lines. Moreover, negative correlations of hsa_circ_0107593 expression were found against tumor diameter, FIGO stage, and myometrial invasion. Also, hsa_circ_0107593 impedes CC cell proliferation, migration, and invasion. Based on ROC curve analysis, hsa_circ_0107593 could serve as a diagnostic biomarker. Its low expression may indicate increased patient’s risk to developing cervical cancer. Mechanistically, hsa_circ_0107593 serves as a sponge of hsa-miR-20a-5p, hsa-miR-93-5p, and hsa-miR-106b-5p. Collectively, our study implies that hsa_circ_0107593 has tumor-suppressing activity in CC by physically binding with hsa-miR-20a-5p, hsa-miR-93-5p, and hsa-miR-106b-5p.